(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRAK This study purposed to find out the utilization of Electronic Government in the Department of Communication, Information, Statistics and Encoding, Luwu Regency. This study used qualitative research with descriptive type. There were eight informants in this study. The research data were collected through observation, interviews, and documentation. Validation of data was done through triangulation of sources, techniques, and past time was analyzed through data collection techniques, data reduction, data presentation and conclusion making. The results showed that the use of Electronic Government at the Communication and Information Office of Luwu Regency from the aspect of the eight elements of a successful e-government project, namely the Political Environment of the Top Down Project (TDP) type, Leadership was quite good. Plan had been realized well. Stakeholders had a high commitment to establish good communication and cooperation. Transparency/visibility could be realized in the form of information contained in the portal managed by the Luwu Regency Diskominfo. Budgets came from the APBD. Technology developed using computerized devices. Innovation by creating an information service system and an integrated service database adapted to an integrated service workflow and integrated with Regional Apparatus Organizations (OPD) Keywords: Utilization, Electronic Government